Functionalization of SiC/SiOx nanowires with a porphyrin derivative: a hybrid nanosystem for X-ray induced singlet oxygen generation. Issue 2 (20th April 2017) - Tatti, R.; Timpel, M.; Nardi, M. V.; Fabbri, F.; Rossi, R.; Pasquardini, L.; Chiasera, A.; Aversa, L.; Koshmak, K.; Giglia, A.; Pasquali, L.; Rimoldi, T.; et al.
Abstract : Singlet oxygen has attracted great attention in physical, chemical, as well as biological studies, mainly due to its high reactivity and strong oxidising properties. Abstract : Singlet oxygen has attracted great attention in physical, chemical, as well as biological studies, mainly due to its high reactivity and strong oxidising properties. In this context, hybrid nanosystems comprised of (inorganic) X-ray absorbing nanostructures and (organic) light-sensitive material (photosensitizers) can potentially overcome the limitations of visible light penetration in matter. A deep investigation of the interface of such hybrid nanosystems for X-ray induced generation of singlet oxygen is key to better understand the processes at the hybrid interface, and to control the energy transfer from inorganic to organic counterparts, which ultimately leads to enhanced singlet oxygen generation. Here, we demonstrate that SiC/SiO x core/shell nanowires functionalized with the tetrakis(pentafluorophenyl)porphyrin can act as a highly promising and viable strategy to generate singlet oxygen, making this novel hybrid nanosystem attractive for applications in photocatalysis and nanomedical applications. Using different excitation sources ( i.e., electrons, visible light, and X-rays) our findings prove that SiC/SiO x core/shell nanowires show X-ray excited optical luminescence, and that optical emission of the photosensitizer is largely enhanced by the nanowires, yielding an efficient energy transfer. A consequent singlet oxygen production of the functionalized nanowires is demonstrated after X-ray excitation in a clinical linear accelerator. These findings will provide an insight in developing an effective route to the molecular functionalization of SiC/SiO x core/shell nanowires and their potential use as singlet oxygen generators.